Dual effects of thermal processing and polyphenol incorporation on bioaccessibility and functionality of soy and whey proteins - Phatcharaporn Khongphakdee; Methavee Peanparkdee; Sudathip Sae-tan (Food Chemistry Advances)
Thermal processing improves safety and shelf life but can alter protein structure and bioactive compound stability. This study investigated the effects of thermal treatments (pasteurization and sterilization) and polyphenol incorporation, specifically free vitexin (V) and vitexin-loaded phytosomes (V-PHN), on the physicochemical properties, bioaccessibility, antioxidant activity, and protein digestibility of soy and whey proteins. Sterilization significantly altered the protein structures, promoting aggregation and unfolding, which influenced total phenolic content (TPC), antioxidant activities, and bioaccessibility. In soy proteins, sterilization increased TPC before digestion but reduced bioaccessibility (31–42 %) and antioxidant activity. In whey proteins, sterilization decreased TPC before digestion but increased it after digestion, suggesting the release of bioactive compounds. Sterilized whey proteins had greater bioaccessibility (104–146 %), suggesting the release of bioactive compounds, but lower antioxidant activity. Digestion enhanced antioxidant activities in both protein systems. V-PHN reduced protein digestibility in non-thermal soy and heat-treated whey proteins but improved TPC and colloidal stability, highlighted protein-polyphenol interactions. These results demonstrate the dual function of polyphenols in stabilizing proteins while regulating their nutritional and functional properties. This study provides important information about the effects of thermal treatment and polyphenol integration to create functional foods with improved stability, bioactivity, and health advantages under industrial processing conditions.